ความรู้เท่าทันสื่อและพฤติกรรมการรู้เท่าทันสื่อเฟซบุ๊ก - สุภิชา มีนิล (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The objectives of this research were 1) to study media literacy levels of Facebook users prior and after media literacy training; 2) to investigate changes in behavior resulting from the training of Facebook users with different levels of media literacy; 3) to gain information about the gap between media literacy and Facebook literacy behavior of users. The study was quasi-experimental using interviews and full participant observations. The subjects were 30 university students in Bangkok who have Facebook accounts and regularly use Facebook at least five days a week. The research findings reveal that the majority of subjects achieve a higher score on the questionnaire regarding media literacy after having been attended the training which points out the fact that the training can potentially help develop people s knowledge on media. In addition, generally, users’ media literacy levels were found to correspond to the way users interacted with Facebook. However, there is also a case where people who appear to have a great score from the questionnaire choose to respond to Facebook posts like they had not known better of it. In consequence, such conflict can lead to the concept that there is still the gap between media literacy and Facebook literacy behavior on people.